Obesity-Related Epigenetic Changes After Bariatric Surgery - Izquierdo, Andrea G.; Crujeiras, Ana B. (Frontiers in Endocrinology, 2019)
Objective: In recent years, an increasing number of studies have begun focusing on epigenetics as a link between environmental factors and a greater predisposition to the development of obesity and its comorbidities. An important challenge in this field is the evaluation of the possibility of the reversal of obesity-related epigenetic marks by means of therapy to induce weight loss and if the beneficial effects of therapy in reducing obesity are mediated by epigenetic mechanisms. We aimed to provide an overview of the recent findings on the impact of bariatric surgery on epigenetic regulation, as well as to show if the beneficial effect of this intervention could be mediated by epigenetic mechanisms. Methods: We conducted a review of the scientific literature in PubMed using key words related to obesity, epigenetics and bariatric surgery to provide an update of recent findings in this area of research. The most relevant and recently published articles and abstracts were selected to frame this review. Results: Previous studies have demonstrated the presence of differential DNA methylation after bariatric surgery and the differential expression of non-coding RNAs. Therefore, epigenetic regulation could mediate the beneficial effect of bariatric surgery on body weight and the metabolic disturbances associated with excess body weight, such as insulin resistance, hypertension, and cardiovascular disease. This evidence is relatively new as epigenetic regulation was first evaluated in the obesity field only a few years ago. However, there is an urgent need to perform longitudinal studies to evaluate the capacity of epigenetic marks in the prediction of bariatric surgery response. Conclusions: Bariatric surgery appears to be capable of partially reversing the obesity-related epigenome. The identification of potential epigenetic marks associated with the response to bariatric surgery may open new doors to personalized therapy for severe obesity.